Permian Mengkarang coal facies and environment, based on organic petrology study - Nana Suwarna (Geological Agency, 2006)
http://dx.doi.org/10.17014/ijog.vol1no1.20061aThe Permian Mengkarang Coal Measures is situated in the middle part of Sumatera Island. Some fresh outcrop samples of the Permian Mengkarang coals have been analyzed both macroscopically and microscopically, to asses their depositional environment. On the basis of organic-petrological analysis, the coal seams show variation in the predominance of some macerals, indicating successions of environmental changes. The dominant maceral group is vitrinite, present in very low to very high values; whilst the minor one is inertinite showing low amount. Environmental information derived from the organic facies study shows that the coals were deposited in wet zone of mire, ranges from wet limnic-telmatic zone to telmatic wet forest swamp under rapid burial condition, due to rapid basin subsidence. The organic facies concept is thus applicable in basin studies context and has potential to become an additional tool for interpretation of depositional environment.